LED substrate, laminate, and method for manufacturing LED substrate
The LED substrate and laminate structure with a reflective layer and adhesive layer address the challenges of reduced brightness and unevenness in mini-LED backlights, enhancing performance and manufacturability.
Patent Information
- Application Number
- JP2021531332
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-15
- Filing Date
- 2021-05-13
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2041-05-13
AI Technical Summary
Mini-LED backlights face challenges with reduced brightness and increased brightness unevenness due to the difficulty in processing reflective films with smaller light sources, leading to reduced yield and increased complexity in adhesion and lamination.
An LED substrate and laminate structure are developed, featuring a reflective layer with a white pigment, a specific void content, and through holes, along with an adhesive layer and a supporting layer, to enhance brightness and uniformity while maintaining a thin profile.
The proposed solution improves the brightness and uniformity of mini-LED backlights, addressing the issues of reduced brightness and unevenness, while also simplifying the manufacturing process and enhancing adhesion accuracy.
Smart Images

Figure 0007666324000004 
Figure 0007666324000005 
Figure 0007666324000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an LED substrate and a laminate. [Background technology]
[0002] In recent years, many liquid crystal displays are used as display devices for personal computers, televisions, mobile phones, etc. These liquid crystal displays are capable of displaying images by irradiating them with light from a surface light source called a backlight installed behind the display.
[0003] The reflective layers used in backlights for liquid crystal displays have traditionally consisted of films containing white pigments or films containing minute air bubbles, either alone or laminated with a metal plate, plastic plate, etc. In particular, films containing minute air bubbles are widely used because they have a certain effect in improving brightness and making the screen brightness uniform (Patent Documents 1 and 2).
[0004] As mobile phones, smartphones and notebook computers become thinner and smaller, and as televisions get larger, there is a demand for reflective layers that are thin yet have high reflectivity, high light shielding properties and high rigidity. In particular, in high-definition LCD televisions, known as 4K and 8K, the transmittance of LCD panels tends to decrease, and a thinner reflective layer with high reflectivity is required.
[0005] A reflective layer is generally constructed using the reflection of light due to the difference in refractive index at the interface between the matrix resin and fine bubbles contained within the film. In order to achieve higher reflectivity, it is necessary to increase the number of interfaces. In order to increase the number of interfaces, the formation of voids using inorganic particles with relatively small particle diameters as nuclei has been considered (Patent Documents 3 and 4).
[0006] Furthermore, when using a reflective layer in a direct-type display, a conventional method involves processing to open a hole in accordance with the position of the light source (LED) and setting the LED so that it shines through the hole (Patent Document 5). [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2003-160682 A [Patent Document 2] Special Publication No. 8-16175 [Patent Document 3] Patent No. 3946183 [Patent Document 4] JP 2013-136232 A [Patent Document 5] JP 2015-106028 A Summary of the Invention [Problem to be solved by the invention]
[0008] In recent years, LED technology (mini-LED technology) has been studied for backlights, which is made by arranging many tiny LEDs on a substrate, in response to the needs for high brightness, high contrast, and wide color gamut of displays. However, when the reflective film described in Patent Documents 1 to 4 is used as the reflective layer of the LED substrate of the mini-LED method, if the LED substrate is manufactured by the method described in Patent Document 5, the difficulty of processing increases due to the miniaturization of the light source (i.e., the size of the hole to be opened) and the yield of the LED substrate manufacturing decreases. Even if the LED substrate can be manufactured, there are problems such as a significant decrease in brightness and a large brightness unevenness compared to the conventional LED method, and a solution was desired. Furthermore, in the mini-LED method, it is preferable to provide an adhesive layer or a pressure-sensitive adhesive layer between the substrate and the reflective film in order to improve the adhesion and lamination accuracy between the two, but in that case, a new problem was found that the presence of the protuberance around the hole, which was not a problem in the conventional LED method, greatly affects the brightness and processability.
[0009] The object of the present invention is to solve the problems of the conventional technology described above, that is, to provide an LED substrate and a laminate that can achieve sufficient brightness even when used in a mini LED type backlight. [Means for solving the problem]
[0010] In view of the above problems, the present inventors have conducted extensive research and found that the above problems can be solved by an LED substrate and a laminate having the following configuration, thereby completing the present invention. [I] An LED substrate having an LED light source and a reflective layer on at least one side of a base material, wherein the reflective layer contains a white pigment, and the protrusion height (P) of the LED light source from the reflective layer is 20 μm or more and 200 μm or less. [II] The LED substrate according to [I], wherein the reflective layer is mainly composed of a polyester resin, and the average void content in a cross section perpendicular to the layer surface of the reflective layer is 10% or more and 70% or less. [III] The LED substrate according to [I] or [II], wherein a ratio (H2 / H1) of a height (H1) of the LED light source to a height (H2) of the reflective layer is 0.1 or more and 0.8 or less. [IV] An LED substrate according to any one of [I] to [III], wherein the reflective layer has one or more through holes, the LED light source is disposed through the through holes in the reflective layer, and the ratio (Sl / Sh) of the area of the LED light source (Sl) to the area of the through holes (Sh) when observed from directly above the surface of the substrate is 0.25 or more and less than 1.00. [V] The LED substrate according to any one of [I] to [IV], wherein the three-dimensional surface roughness SRa of the surface of the reflective layer opposite to the base material is 300 nm or more and less than 2000 nm. [VI] The LED substrate according to any one of [I] to [V], wherein the LED light source is a blue LED light source. [VII] A laminate having at least a reflective layer and an adhesive layer adjacent to each other, wherein the reflective layer has one or more through holes and a protrusion protruding toward the adhesive layer within a 1.0 mm region around the through hole, and the ratio (t / h) of the height (h) of the protrusion to the thickness (t) of the adhesive layer is 0.20 or more and less than 2.00. [VIII] A laminate having at least a release layer, an adhesive layer, a reflective layer, and a support layer in that order, having two or more through holes with a major axis of 0.2 mm or more and 5.0 mm or less that penetrate all of the layers, and the proportion of the through holes in the laminate (opening rate) is 0.1% or more and 60% or less. [IX] A method for manufacturing an LED substrate, comprising: a laminate having at least a release layer, an adhesive layer, a reflective layer, and a support layer in this order, the laminate having a through hole penetrating all of the layers; a step A of removing the release layer from the laminate; a step B of fixing the adhesive layer and a substrate after the step A; and a step C of peeling the support layer from the reflective layer after the step B. Effect of the Invention
[0011] According to the present invention, the brightness of a mini LED type backlight can be improved. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of an LED substrate of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing an example of a laminate of the present invention, illustrating the protrusion height (h) of a protrusion of a reflective layer and the thickness (t) of an adhesive layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The following describes in detail the embodiments of the present invention. However, the present invention should not be construed as being limited to the embodiments including the following examples, and various modifications are possible within the scope of the invention as long as the object of the invention can be achieved and the gist of the invention is not deviated from.
[0014] The LED substrate of the present invention will be described with reference to FIG. 1. As an embodiment of the present invention, as illustrated in FIG. 1, an LED substrate 1 is provided having an LED light source 5 and a reflective layer 3 on at least one side of a base material 2, and the LED light source has a protruding height (P) 6 from the reflective layer of 20 μm to 200 μm. The protruding height (P) here refers to the difference in height between the highest point (the point at which the distance from the substrate is greatest) of the reflective layer close to the LED light source and the highest point (the point at which the distance from the substrate is greatest) of the LED light source. The inventors have found that the decrease in brightness due to the miniaturization of LEDs is caused by the light emitted from the LED light source being blocked by the reflective layer because the highest point of the LED light source is lower than the highest point of the reflective layer. Therefore, by controlling the protruding height (P) of the LED light source to the specific range, the phenomenon in which the light emitted from the LED light source is blocked by the reflective layer and the brightness is reduced can be suppressed, and the brightness unevenness can also be suppressed. By making the protrusion height (P) 20 μm or more, it is possible to suppress the light emitted from the LED light source being blocked by the reflective layer, thereby suppressing the decrease in brightness. On the other hand, by making the protrusion height (P) 200 μm or less, it is possible to suppress the total thickness of the backlight becoming thicker due to the large LED, which hinders the thinning of the display, and the high definition of the display. The protrusion height (P) is preferably 35 μm or more and 120 μm or less, and most preferably 50 μm or more and 70 μm or less. The larger the protrusion height (P), the easier it is to improve the brightness of the backlight in which the LED board is mounted. In addition, the lower the protrusion height (P), the smaller the size of the LED can be, which makes it easier to make the display thinner and to increase the display definition. There is no particular limitation on the method for making the protrusion height (P) of the LED light source from the reflective layer 20 μm or more and 200 μm or less, but for example, a method of adjusting the balance between the height of the LED light source and the thickness of the reflective layer can be mentioned.
[0015] The substrate used in the LED substrate of the present invention is understood to support a conductor pattern having wiring and terminals. The substrate may be one that insulates the conductor patterns from one another, and examples thereof include an insulating resin substrate made of glass epoxy. The substrate used in the present invention is not particularly limited, and materials generally used in LED substrates can be used. Examples of such materials include insulating resin substrates obtained by impregnating a reinforcing material such as glass cloth or paper with a thermosetting resin such as epoxy resin, phenolic resin, or polyimide resin, laminating the layers, and applying heat and pressure; sheet-like substrates containing thermoplastic resins such as LCP, PPS, and thermoplastic polyimide; insulating inorganic substrates such as ceramic; and metal-based substrates in which insulating resins are laminated on metal substrates such as aluminum.
[0016] The LED light source used in the LED substrate of the present invention can be suitably made of, for example, a nitride semiconductor capable of emitting light in the visible range. The LED substrate has at least one LED light source All you need is a LED light source The number of can be changed depending on the purpose and use.
[0017] The reflective layer used in the present invention must contain a white pigment. For example, a white resin layer formed by coating a thermosetting resin containing a white pigment such as titanium oxide on a substrate, or a white resin film containing a white pigment such as titanium oxide and air bubbles can be mentioned. By containing a white pigment, the reflectance of the reflective layer can be improved. In particular, a white resin film is preferably used from the viewpoints of brightness, processability, and color uniformity.
[0018] From the viewpoints of brightness, processability, and color uniformity, the reflective layer in the present invention preferably contains a polyester resin as a main component, and has an average void content of 10% to 70% in a cross section perpendicular to the layer surface of the reflective layer. More preferably, the average void content is 15% to 60%. Here, the main component refers to a component that accounts for 50% by mass or more of the resin components constituting the resin composition.
[0019] A preferred embodiment of the polyester resin is described below. The polyester resin refers to a polymer having an ester bond in the main chain, and the polyester resin used in the present invention is preferably a polyester resin having a structure obtained by condensation polymerization of a dicarboxylic acid and a diol. Examples of the dicarboxylic acid component include aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, 2,6-naphthalenedicarboxylic acid, diphenyldicarboxylic acid, diphenylsulfonedicarboxylic acid, diphenoxyethanedicarboxylic acid, and 5-sodiumsulfonedicarboxylic acid, aliphatic dicarboxylic acids such as oxalic acid, succinic acid, adipic acid, sebacic acid, dimer acid, maleic acid, and fumaric acid, alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid, and oxycarboxylic acids such as paraoxybenzoic acid. Examples of the dicarboxylate derivative component include esters of the above dicarboxylate compounds, such as dimethyl terephthalate, diethyl terephthalate, 2-hydroxyethyl methyl terephthalate, dimethyl 2,6-naphthalenedicarboxylate, dimethyl isophthalate, dimethyl adipate, diethyl maleate, and dimethyl dimerate. Examples of the diol component include aliphatic dihydroxy compounds such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, and 2,2-dimethyl-1,3-propanediol (neopentyl glycol), polyoxyalkylene glycols such as diethylene glycol, polyethylene glycol, polypropylene glycol, and polytetramethylene glycol, alicyclic dihydroxy compounds such as 1,4-cyclohexanedimethanol and spiroglycol, and aromatic dihydroxy compounds such as bisphenol A and bisphenol S. These may be used alone or in combination of two or more. In addition, as long as the film formability is not adversely affected, a small amount of one or more of trimellitic acid, pyromellitic acid and ester derivatives thereof may be copolymerized.
[0020] Specific examples of polyester resins include polyethylene terephthalate (hereinafter abbreviated as PET), polyethylene-2,6-naphthalenedicarboxylate, polypropylene terephthalate, polybutylene terephthalate, and poly-1,4-cyclohexylene dimethylene terephthalate, which are inexpensive and have good film-forming properties and can therefore be particularly suitably used.
[0021] The polyester resin may be either a homopolymer or a copolymer. In the case of a copolymer, the copolymerization components include aromatic dicarboxylic acids, aliphatic dicarboxylic acids, alicyclic dicarboxylic acids, and diol components having 2 to 15 carbon atoms, and examples of these include isophthalic acid, adipic acid, sebacic acid, phthalic acid, sulfonate group-containing isophthalic acid, and ester-forming compounds thereof, ethylene glycol, 1,4-butanediol, neopentyl glycol, 1,4-cyclohexanedimethanol, spiroglycol, and polyalkylene glycols having a number average molecular weight of 400 to 20,000.
[0022] The polyester used in the present invention is preferably a resin having a crystalline fusion heat ΔHm of 20 J / g or more, calculated from the peak area of the melting peak in the differential scanning calorimetry chart obtained by heating the resin from 25°C to 300°C at a heating rate of 10°C / min according to JIS K-7122 (1987), holding the resin at that state for 5 minutes, then quenching at a rate of 40°C / min to 25°C or less, and then heating again from 25°C to 300°C at a heating rate of 10°C / min, according to JIS K-7122 (1987). More preferably, the crystalline fusion heat ΔHm is 25 J / g or more, and even more preferably 30 J / g or more. By using a polyester having a crystalline fusion heat of 30 J / g or more, the height of the protuberance at the periphery of the hole can be reduced when punching a hole.
[0023] The polyester used in the present invention preferably has a carboxyl end group number of 10 equivalents / t or more and 40 equivalents / t or less. More preferably, the carboxyl end group number is 20 equivalents / t or more and 40 equivalents / t or less. By making the carboxyl end group number 10 equivalents / t or more, the height of the protrusion at the periphery of the hole can be kept small when making holes by punching. If the carboxyl end group number exceeds 40 equivalents / t, the catalytic action of the protons derived from the carboxyl end group is strong, hydrolysis and thermal decomposition are promoted, and deterioration of the film may be more likely to proceed.
[0024] The polyester used in the present invention preferably has an intrinsic viscosity of 0.50 or more and 0.90 or less. More preferably, the intrinsic viscosity is 0.55 or more and 0.80 or less, and even more preferably, 0.60 or more and 0.70 or less. By making the IV 0.90 or less, the height of the protuberance at the periphery of the hole can be suppressed to be small when the hole is made by punching. If the IV is less than 0.50, when the void nucleating agent described later is contained to form voids, the entanglement between the molecules becomes too small, and the film breaks frequently, or even if the film can be formed, the mechanical properties may be deteriorated.
[0025] In addition, the reflective layer used in the present invention preferably contains a thermoplastic resin that is incompatible with the main component resin. Here, the term "incompatible" refers to a difference in solubility parameter (hereinafter sometimes abbreviated as "SP value") between the thermoplastic resin and the main component resin by 0.5 (MPa 1 / 2 ) or more. The SP value is the solubility parameter proposed by Hildebrand et al. It is calculated based on the theory of “The Theory of Nonelectrolytes”, [3rd, ed.] Reinhold, NY 1959), and the greater the difference in the SP values of two types of resins, the lower the compatibility of the resins. Incompatible thermoplastic resins are used as void nucleating agents to form voids. Hereinafter, thermoplastic resins that are incompatible with the main component resin will be simply referred to as “void nucleating agents”. When an external force is applied by stretching a resin made by mixing the main component resin and the void nucleating agent in any ratio, the resin around the void nucleating agent is pulled off, forming voids.
[0026] Specific examples of the void nucleating agent include thermoplastic resins such as polyolefin resins, polystyrene resins, polyamide resins, polyimide resins, polyetherimide resins, polyester resins, polyarylene sulfide resins, polyarylene oxide resins, polysulfone resins, polyphenylsulfone resins, aromatic polyether ketone resins, acrylic resins, and fluororesins. Among them, when the main component resin is a polyester resin, linear or branched olefin resins such as polyethylene, polypropylene, polybutene, and polymethylpentene, cyclic olefin resins, styrene resins, poly(meth)acrylate resins, polycarbonate resins, polyacrylonitrile resins, polyphenylene sulfide resins, and fluororesins are preferred. Particularly preferred are olefin resins or styrene resins, and examples of the olefin resins include polyethylene, polypropylene, poly4-methylpentene-1 (hereinafter sometimes abbreviated as "polymethylpentene" or "PMP"), ethylene-propylene copolymers, ethylene-butene-1 copolymers, and cyclic olefins, and examples of the styrene resins include polystyrene, polymethylstyrene, and polydimethylstyrene. These may be homopolymers or copolymers, or two or more of them may be used in combination. In particular, polymethylpentene or cyclic olefin is preferred because it is capable of both functioning as a void nucleating agent and having good film formability.
[0027] The reflective layer used in the present invention preferably contains a white pigment in order to increase the amount of light emitted to the incident surface side due to light scattering and improve the brightness of the display. As the white pigment, among various inorganic particles and organic pigments, particles mainly composed of titanium oxide, calcium carbonate, barium sulfate, zinc oxide, magnesium oxide, silicate, and titanate are preferred in terms of overall effects such as refractive index, void forming ability, whiteness, and optical density, and particles mainly composed of titanium oxide are particularly preferred. If titanium oxide accounts for 50% by mass or more of the components constituting the particles, it can be said that titanium oxide is the main component.
[0028] The white pigment preferably has an average particle size (D50, mode average particle size) of 0.05 to 1.0 μm. More preferably, the average particle size of the white pigment is 0.1 to 0.5 μm, and even more preferably, 0.15 to 0.35 μm. By setting the average particle size of the white pigment to 0.05 μm or more, dispersibility is improved and the occurrence of aggregation is suppressed, and by setting the average particle size to 1.0 μm or less, the occurrence of breakage during film formation can be suppressed.
[0029] When the reflective layer is a white resin film, the white pigment in the reflective layer is preferably more than 10% by mass and less than 40% by mass of all the components constituting the reflective layer. More preferably, the white pigment in the reflective layer is more than 15% by mass and less than 35% by mass. By increasing the white pigment in the reflective layer to more than 10% by mass, the reflectance of the reflective layer is improved, and the height of the protuberance around the hole during hole drilling can be reduced. In addition, by reducing the white pigment to less than 40% by mass, the productivity is improved. In particular, the thinner the film thickness, the more likely the productivity is to decrease, so it is preferable to set the content of the white pigment in the reflective layer within the above range.
[0030] The reflective layer used in the present invention is preferably made of polyester resin as a main component, and the average void content in the cross section perpendicular to the layer surface is 10% or more and 70% or less, since the reflectance of the reflective layer is high. The void in the present invention refers to a gap present in the layer formed by a void nucleating agent or a white pigment. The average void content can be determined by SEM cross-sectional observation and image analysis described later. The voids can be formed by applying an external force by stretching a mixture containing the above-mentioned polyester resin as a main component, the void nucleating agent, and the white pigment, and peeling the polyester resin and the void nucleating agent, or the polyester resin and the white pigment. Specifically, a method of forming voids inside by melt-extruding a mixture containing the polyester resin as a main component, the void nucleating agent, and the white pigment, and then stretching it in at least one direction can be mentioned. By making the average void content 10% or more, the reflectance of the reflective layer can be increased. In addition, by making the average void content 70% or less, breakage during film formation can be suppressed, and productivity can be improved.
[0031] In the LED substrate of the present invention, the reflective layer has one or more through holes, the LED light source is disposed through the through holes in the reflective layer, and the ratio (Sl / Sh) between the area of the LED light source (Sl) and the area of the through holes (Sh) when observed from directly above the surface of the base material is preferably 0.25 or more and less than 1.00. It is preferably 0.50 or more, and more preferably 0.75 or less. By increasing the area ratio (Sl / Sh) between the through holes and the LED light source, the area where the light emitted from the LED light source is reflected by the reflective layer increases, the effect of improving the brightness is enhanced, and brightness unevenness can be suppressed. If the area ratio (Sl / Sh) is too small, the light reflected by the reflective layer decreases, and a problem of reduced brightness may occur. On the other hand, if the area ratio (Sl / Sh) is 0.75 or less, there is an appropriate gap between the LED and the through holes, so that high assembly accuracy is not required during setup, and it is possible to improve the productivity of the LED substrate.
[0032] In the LED substrate of the present invention, the ratio (H2 / H1) of the height (H1) of the LED light source to the height (H2) of the reflective layer is preferably 0.1 or more and 0.8 or less. By making H2 / H1 0.8 or less, it is possible to suppress the light emitted from the LED light source being blocked by the reflective layer, thereby suppressing the decrease in brightness and brightness unevenness. In addition, by making H2 / H1 0.1 or more, it is possible to suppress the total thickness of the backlight becoming thicker due to the large LED light source, which hinders the thinning of the display, and the high definition of the display being hindered. H2 / H1 is preferably 0.1 or more and 0.6 or less, and more preferably 0.1 or more and 0.5 or less. The height (H1) of the LED light source represents the distance between the tip of the LED light source and the surface of the substrate, and the height (H2) of the reflective layer represents the distance between the surface of the reflective layer and the surface of the substrate.
[0033] In addition, the LED substrate of the present invention has an adhesive layer on at least one side of the reflective layer, the reflective layer has one or more through holes and a protuberance protruding toward the adhesive layer within a 1.0 mm area around the through hole, and the ratio (t / h) of the height (h) of the protuberance to the thickness (t) of the adhesive layer is preferably 0.20 or more and less than 1.00. It is preferably 0.50 or more, and more preferably 0.70 or more. By making the ratio (t / h) of the height (h) of the protuberance to the thickness (t) of the adhesive layer 0.20 or more, the protuberance blocks the light emitted from inside the through hole, suppressing a decrease in the brightness of the display, and also improving the adhesion when the reflective layer is attached to a sheet-like material such as a diffusion plate located on the substrate or on the opposite side of the substrate via the adhesive layer. By making the ratio (t / h) less than 1.00, the total thickness of the backlight can be thinned while maintaining the brightness of the display at a good level, which contributes to making the display thinner.
[0034] In the LED substrate of the present invention, the three-dimensional surface roughness SRa of the surface of the reflective layer opposite to the base material is preferably 300 nm or more and less than 2000 nm. By making the three-dimensional surface roughness SRa within the above range, when the light emitted from the LED at a shallow angle is reflected on the surface of the reflective material, it is possible to suppress the light from reaching far inside the backlight, which hinders the high definition of the display. In particular, by making the three-dimensional surface roughness 300 nm or more, it is possible to suppress the case where the unlit part appears bright due to the light from the lit part when the backlight is partially driven. In addition, by making the three-dimensional surface roughness 2000 nm or less, it is possible to suppress the cost of processing and increase the yield. It is more preferably 500 nm or more. There is no particular limitation on the method of making the surface roughness within the above range, but it is preferable that the reflective material has a layer containing particles or beads for forming unevenness.
[0035] In the LED substrate of the present invention, the LED light source is preferably a blue LED light source. When the LED substrate of the present invention has a plurality of LED light sources, it is preferable to have one or more LED light sources. When a blue light source, which has a short wavelength among visible light, is used as the light source, the problem that the light emitted from the LED light source is blocked by the reflective layer occurs more severely, so that it is preferable to obtain the effect of improving the brightness according to the present invention more effectively.
[0036] The laminate of the present invention will be described with reference to FIG. 2. As an embodiment of the present invention, as illustrated in FIG. 2, a laminate having at least a reflective layer 3 and an adhesive layer 4 adjacent to each other, the reflective layer has one or more through holes 14 and a protuberance 9 protruding toward the adhesive layer within a 1.0 mm region 8 around the through holes, and the ratio (t / h) of the height (h) 11 of the protuberance to the thickness (t) 12 of the adhesive layer is 0.20 or more and less than 2.00. The laminate at the depth of the through holes 14 is omitted from the drawing. Here, the 1.0 mm region around the through holes refers to the region contained in a concentric circle with a radius of 1.0 mm, starting from the center of gravity of the through holes when the reflective layer is viewed from directly above the surface, and is determined by the measurement method described later. The height (h) of the protuberance refers to the height at which the reflective layer protrudes most toward the adhesive layer within a 1.0 mm region around the through holes. t / h is more preferably 0.50 or more, and even more preferably 0.70 or more. By setting the ratio (t / h) of the height (h) of the raised portion to the thickness (t) of the adhesive layer to be 0.20 or more, when the laminate is laminated to a substrate so that the LED is placed in the through-hole of the laminate to create an LED substrate, the raised portion blocks the light emitted from inside the LED through-hole, suppressing a decrease in the brightness of the display, and improving adhesion when laminated to the substrate. In addition, by setting the ratio (t / h) to be less than 2.00, it is possible to suppress misalignment during lamination processing due to the adhesive layer being too thick. In addition, when the laminate is combined with a substrate or an LED light source to an LED substrate, it is possible to reduce the total thickness of the backlight while maintaining good brightness of the display, thereby contributing to a thinner display.
[0037] The thickness (t) of the adhesive layer is preferably 0.1 μm or more and 25 μm or less. More preferably, it is 0.5 μm or more and 20 μm or less, and even more preferably, it is 1 μm or more and 15 μm or less. If the thickness is less than 0.1 μm, the adhesive strength may be insufficient. If the thickness is more than 25 μm, the height of the protrusions around the holes may become high during the hole drilling process, or the position may become significantly misaligned during the lamination process.
[0038] The height (h) of the raised portion is preferably 25 μm or less, more preferably 20 μm or less, and further preferably 15 μm or less. If the height of the raised portion is more than 25 μm, the adhesion when bonding to a substrate may decrease.
[0039] As an embodiment of the present invention, as illustrated in FIG. 2, there is a laminate having at least a peeling layer 13, an adhesive layer 4, a reflective layer 3, and a support layer (not shown) in this order, and having two or more through holes 14 with a major axis of 0.2 mm to 5.0 mm that penetrate all layers, and a ratio (aperture ratio) of the through holes in the laminate of 0.1% to 60%. The above-mentioned through holes are for arranging LEDs, and the size, shape, and ratio of the through holes in the laminate in-plane direction are changed according to the size and number of LEDs. By making the major axis of the through holes 5.0 mm or less, the through holes do not become too large compared to the size of the LEDs of the mini LED method, and light can be sufficiently reflected. By making the major axis of the through holes 0.2 mm or more, a decrease in yield due to a misalignment during processing to align the position of the LEDs with the position of the holes can be suppressed. More preferably, it is 0.3 mm to 3.0 mm, and even more preferably, it is 0.4 mm to 2.5 mm. Moreover, by making the aperture ratio 0.1% or more, it is possible to arrange the number of LEDs that will provide a sufficient amount of light. Moreover, by making the aperture ratio 60% or less, it is possible to maintain the shape of the laminate as a film and improve the reflection performance. More preferably, it is 0.3% or more and 50% or less, and further preferably, it is 0.5% or more and 40% or less. Although the object of the present invention is to arrange the LED in the through hole, there is no problem in arranging a component other than the LED in the through hole as long as it does not impair the effect of the present invention. Moreover, the shape and size of the through hole do not have to be constant. In that case, it is preferable that the major axis of 90% or more of the through holes out of the total number of the through holes is 0.2 to 5.0 mm.
[0040] Next, an example of a method for producing the through-holes in the LED substrate and the reflective layer of the present invention will be described. The processing can be mechanical processing, chemical etching, or a combination of these. Examples of mechanical processing include drilling with a drill bit or a press processing, Thomson processing, and embossing roll processing. Examples of chemical etching include laser processing using a CW laser or a pulsed laser. Among them, punching methods such as press processing, Thomson processing, and embossing roll processing are particularly preferably used from the viewpoint of productivity.
[0041] In the present invention, the thickness of the reflective layer is preferably 80 μm or less. The thickness of the reflective layer is preferably 65 μm or less. By making the thickness of the reflective layer 80 μm or less, when a mini-LED type LED light source is used, the light shielding by the reflective layer can be suppressed, and the brightness can be improved. In addition, the thickness of the reflective layer is also preferably 20 μm or more. By making the thickness of the reflective layer 20 μm or more, the reflectance of the reflective layer can be sufficiently increased. In addition, for example, when a white resin film is used as the reflective layer, the film forming property and the handling property during processing can be improved. More preferably, it is 30 μm or more. In addition, when the through hole in the present invention is made by the punching method described later, if the thickness of the reflective layer is thick, the height (h) of the protrusion protruding to the adhesive layer side within a 1.0 mm area around the through hole tends to be high.
[0042] In the present invention, the method for making the reflective layer thickness fall within the above-mentioned preferred range is not particularly limited. However, in the case of using a white resin film for the reflective layer, in the conventional material, the reduction in the reflective layer thickness is in a trade-off relationship with the reflectance, so it is difficult to achieve both. Due to the influence of the white pigment added in large amounts to increase the reflectance and the voids formed by the stretching process, when the film thickness is set to 80 μm or less, the film formability is significantly deteriorated, making it difficult to make the film itself. To address this issue, it is preferable to perform a surface treatment to increase the compatibility between the white pigment and the resin. As the surface treatment agent, silicone, a silane coupling agent, an aluminum chelating agent, polyurea, etc. are preferably used. Particularly preferred is a silane coupling agent. It is also preferable to melt-knead the surface-treated white pigment particles with the void nucleating agent to obtain a master batch, and then melt-knead the resin, which is the main component of the reflective layer, with the master batch to obtain a structure in which the white pigment particles are contained inside the void nucleating agent.
[0043] The LED substrate of the present invention preferably has an LED light source with a height of 250 μm or less. More preferably, it is 100 μm or less. Conventionally, LED light sources with a height of 1 mm or more have been used. When performing delicate display, the number of LED light sources is increased, but the manufacturing cost associated with the cost of increasing the LED light sources has been an issue. In addition, when changing a normal flat display to a curved display, there is a problem that the desired curved shape cannot be realized due to the size and rigidity of the LED. LED light sources with a height in the above-mentioned range are suitable for mass production using a chip-on-board method in which the LED light sources are directly mounted on the substrate, so the cost of mass production is cheaper than when an LED light source with a height of 1 mm or more is used, which reduces the cost when the number of LED light sources is increased. In addition, by using an LED light source with a height in the above-mentioned range, it is possible to achieve conformity to a curved shape, and it can be preferably used for thin liquid crystal display applications.
[0044] An example of the manufacturing method of the LED substrate of the present invention includes a manufacturing method including step A of removing the peeling layer from the laminate having at least the peeling layer, adhesive layer, reflective layer, and support layer in this order and having a through hole penetrating all layers, step B of fixing the adhesive layer and the substrate after step A (fixing the adhesive layer and the substrate of the laminate from which the peeling layer has been removed), and step C of peeling the support layer from the reflective layer (removing the support layer from the laminate attached to the substrate) after step B. By such a manufacturing method, an LED substrate having a thin and highly reflective reflective layer can be obtained with high productivity.
[0045] Next, an example of a method for producing the laminate of the present invention will be described, but the method is not particularly limited to this example. As shown below, an example of a method for producing the laminate can be mentioned in which a release layer, a reflective layer, and a support layer are each produced, and then the layers are laminated together in a post-process.
[0046] First, a method for producing a reflective layer included in the laminate of the present invention will be described using a three-layer laminate film as an example, but the present invention is not particularly limited to this example, and may be a single layer or a laminate structure other than three layers. In a composite film-forming device having at least two single-screw or twin-screw extruders, a main extruder and a sub-extruder, a resin as a raw material for the core layer (Y) is fed into the main extruder, and a resin as a raw material for the surface layer (X) is fed into the sub-extruder. It is preferable that each raw material is dried so that the moisture content is 50 ppm or less. In this way, the raw materials are supplied to each extruder, and a three-layer laminate film of X / Y / X can be formed, for example, by two extruders and a feed block or multi-manifold installed above a T-die. The extruded unstretched sheet is cooled and solidified in close contact on a cooled drum to obtain an unstretched laminate film. At this time, it is preferable to apply static electricity to make the film adhere to the drum in order to obtain a uniform film.
[0047] The unstretched film is heated to a temperature equal to or higher than the glass transition temperature (Tg) of the polymer by roll heating, or infrared heating if necessary, and stretched in the longitudinal direction (hereinafter, sometimes referred to as longitudinal stretching) to obtain a longitudinally stretched film. This stretching is performed by utilizing the peripheral speed difference between two or more rolls. The longitudinal stretching ratio is preferably 2 to 6 times, more preferably 3 to 4 times, depending on the required characteristics of the application. By setting it to 2 times or more, the reflectance can be increased, and by setting it to 6 times or less, breakage during film formation can be suppressed. The film after the longitudinal stretching is then stretched in a direction perpendicular to the longitudinal direction (hereinafter, sometimes referred to as transverse stretching), heat set, and heat relax in sequence to obtain a biaxially oriented film, and these treatments are preferably performed while the film is running. At this time, the preheating and stretching temperatures for the transverse stretching are preferably performed at a temperature equal to or higher than the glass transition temperature (Tg) of the polymer (Tg+20°C). The transverse stretching ratio is preferably 2.5 to 6 times, more preferably 3 to 4 times, depending on the required characteristics of the application. By setting the ratio to 2.5 or more, the reflectance can be increased. By setting the ratio to 6 or less, breakage during film formation can be suppressed. In order to complete the crystal orientation of the obtained biaxially oriented film and impart flatness and dimensional stability, the film is subsequently heat-treated in a tenter at a temperature of 180 to 230°C for 1 to 60 seconds, uniformly cooled slowly, cooled to room temperature, and wound on a roll. The heat treatment may be performed while relaxing the film by 3 to 12% in the longitudinal and / or transverse directions.
[0048] Although the case where stretching is performed by the sequential biaxial stretching method has been described in detail here, the stretching may be performed by either the sequential biaxial stretching method or the simultaneous biaxial stretching method, and further, if necessary, re-longitudinal stretching and / or re-transverse stretching may be performed after the biaxial stretching.
[0049] In addition, to the extent that the effects of the present invention are not impaired, at least one surface of each polyester film may be coated with various coating liquids using well-known techniques in order to impart lubricity, antistatic properties, ultraviolet light absorption performance, etc., or a hard coat layer may be provided in order to enhance impact resistance. Coating may be performed during film production (in-line coating) or on the polyester film after film production (off-line coating).
[0050] Next, the method for producing the release layer used in the present invention will be described. As the method for producing the release layer, a polyester film is produced in the same manner as the above-mentioned method for producing the reflective layer, and then a release agent is applied and dried to impart releasability. The method for applying and drying the release agent may be either an in-line coating method performed during polyester film production or an off-line coating method performed after polyester film production.
[0051] Next, the manufacturing method of the support layer used in the present invention will be described. As a manufacturing method of the support layer, a method of manufacturing a polyester film in the same manner as the manufacturing method of the reflective layer, and then coating and drying a weak adhesive layer to impart weak adhesiveness can be mentioned. The method of coating and drying the weak adhesive layer may be either an in-line coating method performed during polyester film formation or an off-line coating method performed after polyester film formation. In addition, a pigment may be appropriately added to the weak adhesive layer for identification.
[0052] Next, a method of laminating the release layer, the reflective layer, and the support layer in a later process will be described. First, an adhesive layer is applied to a polyester film that will become the reflective layer, and after drying, it is laminated with the release layer. A slightly adhesive layer containing a colorant is applied to the support layer, dried, and laminated to the reflective layer side of a laminated polyester film consisting of a release layer / adhesive layer / reflective layer to obtain a laminate. The adhesive layer is a layer having a peel strength of 2N / 25mm or more as measured in a 180° peel test described in JIS Z 0237:2009, and the slightly adhesive layer is a layer having a peel strength of 0.01N / 25mm or more and less than 2N / 25mm as measured in a 180° peel test described in JIS Z 0237:2009.
[0053] Next, an example of a specific manufacturing method of the LED substrate of the present invention will be described, but is not particularly limited. A single-sided copper foil laminate is prepared, and an etching resist is formed on the copper foil by a printing method, and then etching is performed to form a conductor pattern having wiring and terminals for mounting LEDs on one side of the insulating substrate, thereby obtaining a substrate. Next, an LED light source (for example, a rectangular parallelepiped blue LED light source with a light-emitting part height of 100 μm and length and width of 300 μm) is connected to the conductor pattern of the substrate formed above.
[0054] Next, a through hole of a desired size is formed in the laminate obtained by the above-mentioned method at a position corresponding to the position of the LED light source of the substrate to which the LED light source is connected. The through hole can be formed by a known method such as a method using a drill or a laser, or punching using a Thomson blade, a press die, or an embossing roll, but the punching method is preferably used from the viewpoint of productivity. By forming a through hole from the support side of the laminate using a punching method, a protrusion protruding to the adhesive layer side is formed within a 1.0 mm area around the through hole. At this time, the height of the protrusion protruding to the adhesive layer side can be controlled by controlling the clearance between the male and female dies of the punching die. When the clearance between the male and female dies of the punching die is reduced, the height of the protrusion protruding to the adhesive layer side tends to be reduced. The clearance between the male and female dies of the punching die is 10 μm or more and 75 μm or less, more preferably 20 μm or more and 50 μm or less. The laminate is then cut to the same size as the substrate connected to the LED light source, the release layer is removed from the laminate, and the LED light source and the through hole are then aligned so that the adhesive layer faces the substrate to fix the adhesive layer to the substrate, and then the support layer is peeled off from the laminate to obtain the LED substrate of the present invention. EXAMPLES
[0055] The present invention will be described in detail below with reference to examples. The respective property values were measured by the following methods.
[0056] (1) Height of the LED light source (H1), height of the reflective layer (H2), height of the LED light source protruding from the reflective layer (P), ratio of the height of the reflective layer to the height of the LED light source (H2 / H1) The LED substrate was observed from the side, i.e., from the vertical cross-sectional direction, with an electron microscope (S-2100A type, manufactured by Hitachi, Ltd.) at an appropriate magnification (100x to 5000x as a guide), and the distance between the tip of the LED light source and the surface of the substrate was measured and determined as the height of the LED light source (H1). The distance between the reflective layer surface and the surface of the substrate was measured in the same manner and determined as the height of the reflective layer (H2). The distance between the tip of the LED light source and the surface of the reflective layer was measured in the same manner and determined as the protrusion height (P). When observation from the side was difficult, the entire LED substrate was cut perpendicular to the reflective layer surface with a diamond cutter so as not to deform it, and then the cross section was finished cut using an ion milling device and observed with an electron microscope. The ratio (H2 / H1) of the height of the LED light source (H1) and the height of the reflective layer (H2) was calculated by dividing H2 by H1.
[0057] (2) Area of the through hole (Sh), area of the LED light source (Sl), ratio of the LED light source area to the through hole area (Sl / Sh), and major axis of the through hole The LED substrate was observed from directly above the surface of the substrate with an electron microscope (LEICA DMLM, Leica Microsystems) at a magnification of 100 times, and the area of the through-holes in the reflective layer (Sh) was calculated. The area of the LED light source (Sl) was calculated in the same manner. The ratio of the area of the LED light source (Sl) to the area of the through-hole (Sl / Sh) was calculated by dividing Sl by Sh. The long diameter of the through-hole was obtained by observing the shape of the hole from directly above the surface, and the long diameter was calculated as the distance between the two farthest points of the two intersections between the line passing through the center of gravity and the edge of the hole. (If the hole is a perfect circle, the long diameter = diameter.) In addition, if there are multiple through-holes or LED light sources in the substrate, the area and long diameter of each were calculated for all of them, and the average value was used. However, through-holes without an LED light source installed were excluded from the calculation of the average area of the through-holes.
[0058] (3) Aperture ratio When the laminate was in the form of a cut sheet, the area of all the holes was calculated, and then the area of the smallest rectangle containing all the holes was used as the denominator to calculate the aperture ratio (%). When the laminate was in the form of a roll or had a large number of holes, making it practically difficult to measure all the holes, and the arrangement of the openings had a repeating pattern, the aperture ratio was calculated based on the repeating unit.
[0059] (4) Height (h) of the protrusion within a 1.0 mm area around the through hole, thickness (t) of the adhesive layer, and ratio (t / h) of the adhesive layer thickness to the height of the protrusion within a 1.0 mm area around the through hole The description will be given with reference to FIG. 2. The laminate or LED substrate was cut vertically with a diamond cutter so as not to deform the laminate, and then the vertical cross section was prepared. The cross section was then finished cut using an ion milling device, and the cross section was observed with an electron microscope. The cross section image was imported into image analysis software, and three points on the surface of the reflective layer, which were located at least 2.0 mm apart from each other and 1.1 mm apart from the center of gravity of the through hole when the reflective layer was viewed from directly above the surface, were selected to determine the reflecting layer surface baseline 7. Next, the center of gravity of the through hole when the reflective layer was viewed from directly above the surface was used as the starting point, and the area included in a concentric circle with a radius of 1.0 mm was set as the 1.0 mm area 8 around the through hole, and the height of the maximum point 10 of the protruding part of the reflective layer protruding toward the adhesive layer side based on the baseline within the 1.0 mm area around the through hole was obtained. The same calculation was performed for 100 through holes, and the average of the maximum heights of the 100 through holes was set as the height (h) 11 of the protruding part within the 1.0 mm area around the through hole. In addition, the thickness of the adhesive layer in contact with the surface of the reflective layer on the side where the protuberance was present within a 1.0 mm region around the through-hole was calculated and designated as the adhesive layer thickness (t) 12. The ratio (t / h) of the adhesive layer thickness to the height of the protuberance within a 1.0 mm region around the through-hole was calculated by dividing t by h.
[0060] (5) Surface roughness (SRa) After the reflective surface of the reflective layer (the surface opposite to the substrate) was exposed, the surface of the reflective layer was observed in three dimensions from directly above using a Keyence Corporation shape analysis laser microscope VK-X1000 (head part VK-X1100) to determine the three-dimensional surface roughness SRa value. The measurement range was a 150 μm square range on the surface of the reflective layer, avoiding the through holes. The measurement resolution in the height direction was 0.5 nm, the display resolution in the surface direction was 1 nm, and the refresh rate was 125 Hz. The measurement was performed five times at different measurement positions within the sample, and the average value of the obtained SRa values was used as the final SRa value of the sample.
[0061] (6) Relative luminance The LED substrate prepared in the examples described below was made to emit light, and photographed with a CCD camera (DXC-390 manufactured by SONY) from a point 90 cm directly above the LED substrate, and an image of a range of 20 mm x 20 mm was captured with an image analyzer (CA-2000 manufactured by Konica Minolta), and the brightness level was controlled to 30,000 steps and automatically detected, and the brightness was calculated. In addition, an LED substrate was prepared without only the reflective layer, and the brightness was measured in the same manner. The brightness of the LED substrate having the reflective layer was divided by the brightness of the LED substrate without the reflective layer to obtain the relative brightness. The same measurement was performed on five arbitrary positions of the LED substrate whose centers were 30 mm or more apart, and the average value of the five relative brightness values obtained was used as the relative brightness of the sample, and the obtained relative brightness was evaluated according to the following criteria. A: 130% or more B: 120% or more but less than 130% C: 100% or more but less than 120% D: Less than 100%.
[0062] (7) Uneven brightness In the measurement of relative luminance in (6), five relative luminance values were measured at five arbitrary points, and the luminance unevenness (%) was calculated using the following formula. Luminance unevenness (%) = {(maximum of five relative luminance values) - (minimum of five relative luminance values) / (average of five relative luminance values)} x 100 The luminance unevenness and the condition of the sample were evaluated according to the following criteria. A: Luminance unevenness is less than 2.0% B: Luminance unevenness is 2.0% or more and less than 5.0% C: Luminance unevenness is 5.0% or more and less than 10.0% D: Brightness unevenness is 10.0% or more.
[0063] (8) Processability In the examples described later, the laminate with through holes formed therein and the substrate equipped with the LED light source were fixed with a laminator at a linear pressure of 5 kgf / cm, the support layer was peeled off, and the LED substrate was fabricated. The processability was evaluated according to the following criteria. A: Processing was possible without any problems. B: There was some misalignment and uneven adhesion, but it did not affect use. C: When the support layer was peeled off, the substrate and the reflective layer peeled off, or the reflective layer was deformed.
[0064] (9) Average void content Using an ion milling device (IM4000 manufactured by Hitachi), the film was cut perpendicular to the film surface while being cooled by liquid nitrogen to suppress deformation and damage to the film, and a measurement sample was prepared. The cutting direction was rotated in-plane to the right at 5° intervals relative to the film surface, and a vertical cross section was prepared at each rotation angle, until the total rotation angle reached 90°, and a total of 19 vertical cross-sectional samples were prepared. After depositing platinum-palladium on the prepared cross sections, the film cross section was observed from directly above using a shape analysis laser microscope (VK-X1000 manufactured by Keyence, head part is VK-X1100), and the cross-sectional shape was measured by mapping. The measurement conditions were set to those that provided the highest display resolution. When the film was composed of multiple layers, the thickest layer was observed, and the target area range of the sample cross section to be observed by mapping was 10,000 to 22,500 μm in total. 2 The observation was performed so that the cross-sectional analysis data obtained was such that the highest point was defined as the cut surface, and the height of the cut surface was used as the reference height, with the parts with heights of -50 to 0 nm being white regions (brightness 100) and parts with heights of less than -50 nm being black regions (brightness 0), and the observation data was binarized. The area Sw of the white regions and the area Sb of the black regions were calculated using analysis software (included with the device), and the void content V was calculated based on the following formula. V = Sb / (Sw+Sb) × 100 ... (equation).
[0065] The void content V was calculated for all 19 vertical cross sections, and the average value was taken as the average void content.
[0066] [Raw materials used] (1) Polyester resin (a) Polyethylene terephthalate (PET) was obtained by polymerization of terephthalic acid and ethylene glycol using antimony trioxide as a catalyst in the usual manner. The glass transition temperature of the obtained PET was 77°C, the melting point was 255°C, the intrinsic viscosity was 0.63 dl / g, the heat of crystal fusion was 35 J / g, and the terminal carboxyl group concentration was 40 equivalents / t.
[0067] (2) Thermoplastic resin (b) Commercially available cyclic olefin resin "TOPAS 6017" (Japan Polyplastics Co., Ltd.) Company) was used.
[0068] (3) Titanium dioxide masterbatch (c) 0.25 parts by mass of a silane coupling agent "11-100 Additive" (manufactured by Dow Corning Toray Co., Ltd.) was added to 50 parts by mass of titanium dioxide particles (number average particle size 0.25 μm, rutile type) and surface-treated by a conventional method. The mixture was then kneaded with 50 parts by mass of polyester resin (a) in a twin-screw extruder to obtain titanium dioxide master pellets (c).
[0069] (4) Aggregated Silica Master (d) The aggregated silica particles (number average particle diameter 4.0 μm) were kneaded with a particle concentration of 10 parts by mass and polyester resin (a) of 90 parts by mass in a twin-screw extruder to obtain a silica master (d).
[0070] Example 1 [Peeling layer] A 38 μm thick polyethylene terephthalate film with a silicone release agent (PET38X manufactured by Lintec Corporation) was used.
[0071] [Reflective layer: polyester film] After the raw materials having the composition shown in Table 2 were vacuum-dried at a temperature of 180°C for 6 hours, the raw materials for the core layer (Y) were supplied to the main extruder, melt-extruded at a temperature of 280°C, and filtered through a 30 μm cut filter. In addition, the raw materials for the surface layer (X) were supplied to the sub-extruder, melt-extruded at a temperature of 290°C, and filtered through a 30 μm cut filter. Subsequently, these molten polymers were merged in a T-die composite die so that the surface layers were laminated on both surface layers of the core layer (X / Y / X). Subsequently, the merged molten polymers were extruded into a sheet shape to form a molten sheet, and the molten sheet was adhered to a drum whose surface temperature was kept at 25°C by an electrostatic application method, cooled and solidified to form an unstretched film. Subsequently, the unstretched film was preheated with a group of rolls heated to a temperature of 80°C, and then stretched longitudinally (stretched in the film longitudinal direction) at the ratio shown in Table 2 while irradiating both sides with infrared heaters, and cooled with a group of rolls at a temperature of 25°C to form a uniaxially stretched film. Subsequently, while both ends of the uniaxially stretched film were held with clips, the film was introduced into a 90°C preheating zone in a tenter, and transversely stretched (stretched in the film width direction) at 95°C at the ratio shown in Table 2. Subsequently, the film was subjected to heat treatment at the temperature shown in Table 2 in the heat treatment zone in the tenter, and then uniformly cooled slowly and then wound up on a roll to obtain a biaxially oriented polyester film (reflective layer) having the thickness shown in Table 2.
[0072] [Adhesive layer: silicone resin] A mixture of 100 parts by mass of silicone resin adhesive (SH4280PSA, manufactured by Dow Corning Toray Co., Ltd.), 0.15 parts by mass of benzoyl peroxide catalyst (Niper(R) BMT-K40, manufactured by NOF Corporation), and 50 parts by mass of toluene was applied to the film that would become the reflective layer so that the adhesive layer would have a thickness after drying as shown in Table 1-1, and the film was heated and cured at 70°C for 3 minutes and then at 180°C for 5 minutes.
[0073] [Support layer] A solution containing 100 parts of an acrylic copolymer (SK Dyne 1499M, Soken Chemical Industries, Ltd., solid content concentration 30% by mass), 5.4 parts of an isocyanate crosslinking agent (Coronate L, Nippon Polyurethane Co., Ltd., solid content concentration 75% by mass), and 5 parts of a green pigment (NAF1063 Green, Dainichi Seika Chemicals Co., Ltd.) was applied to a polyethylene terephthalate film (Lumirror (R) T60, Toray Industries, Inc.) so that the thickness after drying was 3 μm, and then dried at about 80 ° C. for 1 minute and further aged at 40 ° C. for 72 hours to form a support layer. A polyethylene terephthalate film of 150 μm was used.
[0074] [Laminate] A release layer, an adhesive layer, a reflective layer and a support layer were laminated in this order to obtain a laminate having no through holes.
[0075] [Substrate equipped with LED light source] A resin substrate with a long side (horizontal direction) of 140 mm and a short side (vertical direction) of 76.4 mm was used to arrange blue LED light sources of the size shown in Table 1-2 in parallel at the pitch shown in Table 1-1, to prepare a substrate equipped with LED light sources. The pitch was the same both vertically and horizontally, and the LEDs were installed so as to completely cover the entire surface. The term "pitch" refers to the spacing between objects arranged at equal intervals in design drawings, and in the present invention refers to the spacing between the centers of the LED light sources when viewed directly above the surface of the substrate.
[0076] [LED board] The laminate obtained by the above method was processed to open circular through holes with the through hole area and through hole major diameter per hole as shown in Tables 1-1 and 1-2, using a die press with a male-female clearance of 55 μm. The positions of the holes were adjusted so that the center of each LED light source coincided with the center of each hole when the LED-mounted substrate was observed from directly above the surface.
[0077] Next, the release layer was removed from the laminate, and the LEDs were placed on the LED-mounted substrate so that they would fit into the through-holes, and fixed with a laminator at a linear pressure of 5 kgf / cm, after which the support layer was peeled off. An acrylic diffusion plate was then placed on top of the LED so that the gap between the blue LED was 5 mm, and a prism sheet was placed on top of the acrylic diffusion plate. The LED substrate was then left to stand for 1 hour under conditions of 25°C temperature and 65% relative humidity to produce an LED substrate.
[0078] (Examples 2 to 9, Comparative Examples 1 to 4) An LED substrate was produced in the same manner as in Example 1, except that the conditions were as shown in Tables 1-1 and 1-2.
[0079] In Comparative Example 3, the LED substrate could not be manufactured because of the large positional deviation during lamination processing. In Comparative Example 4, the reflective layer was deformed when the support layer was peeled off, and the LED substrate could not be manufactured.
[0080] Example 10 An LED substrate was produced in the same manner as in Example 3, except that the drilling process was carried out using a die press with a clearance between the male and female dies of 40 μm.
[0081] Example 11 [Reflective layer 7: polyester film] After obtaining the reflective layer 2 described in Table 2, a coating material having the following composition was applied to a thickness of 3 μm after drying, and then dried at a temperature of 120° C. for 2 minutes to obtain a polyester film (reflective layer 7) having the surface roughness described in Table 1-2. Binder: HALSHYBRID (registered trademark) UV-G720T (solid content 40% by mass, manufactured by Nippon Shokubai Co., Ltd.): 10 parts by mass, hardener: DURANATE 24A-100 (manufactured by Asahi Kasei Chemicals Co., Ltd.): 0.4 parts by mass, beads: ORGASOL (registered trademark) 1002 UD NAT 1 (porous nylon 6 resin particles, manufactured by Arkema Co., Ltd., average particle size 5 μm): 4.6 parts by mass Parts by weight, solvent: ethyl acetate: 12 parts by weight.
[0082] An LED substrate was produced in the same manner as in Example 2, except that the reflective layer 7 was used as the reflective layer.
[0083] Example 12 An LED substrate was produced in the same manner as in Example 2, except that the following polyester film (reflective layer 8) was used as the reflective layer. [Reflective layer 8: polyester film] Raw materials consisting of 60% by mass of polyester resin (a), 20% by mass of thermoplastic resin (b), and 20% by mass of titanium dioxide master (c) were vacuum-dried at a temperature of 180°C for 6 hours, and then fed to a main extruder, melt-extruded at a temperature of 280°C, and filtered through a 30 μm cut filter. Subsequently, the molten polymer was extruded into a sheet shape from a T-die to form a molten sheet, and the molten sheet was brought into contact with a drum whose surface temperature was kept at 25°C by electrostatic application method, cooled and solidified to form an unstretched film. Subsequently, the unstretched film was preheated with a group of rolls heated to a temperature of 80°C, and then longitudinally stretched (stretched in the film longitudinal direction) at the ratio in Table 2 while irradiating both sides with an infrared heater, and cooled with a group of rolls at a temperature of 25°C to form a uniaxially stretched film. Subsequently, the uniaxially stretched film was guided to a 90°C preheating zone in a tenter while holding both ends with clips, and transversely stretched (stretched in the film width direction) at 95°C at the ratio in Table 2. Subsequently, the film was subjected to heat treatment at the temperature shown in Table 2 in the heat treatment zone of the tenter, then uniformly cooled slowly and then wound up on a roll to obtain a biaxially oriented polyester film (reflective layer 8) having the thickness shown in Table 2.
[0084] (Example 13, Comparative Example 5) [Substrate equipped with LED light source] A resin substrate with a long side (horizontal direction) of 140 mm and a short side (vertical direction) of 76.4 mm was prepared by arranging blue LED light sources of the size shown in Table 1-2 in parallel at the pitch shown in Table 1-1 on the substrate. The pitch was the same both vertically and horizontally, and the LEDs were installed so as to completely cover the entire surface.
[0085] [Reflective layer] Next, a thermosetting white solder resist S500 (LEW51) (manufactured by Taiyo Ink Mfg. Co., Ltd.) was applied as a reflective layer to the surface of the substrate by screen printing, and heat treatment (150°C, 30 minutes) was repeated so that the height (P) of the protruding portion of the LED light source from the reflective layer, the ratio (H2 / H1) of the height of the LED light source (H1) to the height of the reflective layer (H2), etc., were as shown in Table 1-2. The reflective layer was printed with holes avoiding the LED light source area, and the size of the holes was 0.4 mm per LED light source. 2 The hole was designed so that the center of the hole overlaps with the center of the LED light source when the substrate was observed from directly above the surface.
[0086] [Adhesive layer] A mixture of 100 parts by mass of silicone resin adhesive (SH4280PSA, manufactured by Dow Corning Toray Co., Ltd.), 0.15 parts by mass of benzoyl peroxide catalyst (Niper(R) BMT-K40, manufactured by NOF Corporation), and 50 parts by mass of toluene was applied to the surface of the reflective layer provided on the surface of a substrate equipped with an LED light source, so that the adhesive layer would have a thickness as shown in Table 1-1 after drying, and the adhesive layer was cured by heating at 70°C for 3 minutes and at 180°C for 5 minutes to provide an adhesive layer. The application was performed using a screen printing method, with holes printed to avoid the LED light source area, and the size of each hole was 0.4 mm. 2 The holes were aligned so that they overlapped with the holes in the reflective layer when viewed from directly above the surface of the base material.
[0087] [LED board] Next, an acrylic diffusion plate was placed on top of it so that the gap between it and the blue LED was 5 mm, and then a prism sheet was placed on top of that. The resulting mixture was left to stand for 1 hour under conditions of a temperature of 25° C. and a relative humidity of 65%, to produce an LED substrate.
[0088] Comparative Example 6 An attempt was made to fabricate an LED substrate in the same manner as in Example 2, except that a peel-off layer, adhesive layer, and reflective layer were laminated in that order and a laminate without a support layer was used; however, the laminate could not be sufficiently adhered to the base material, and an LED substrate could not be fabricated.
[0089] Comparative Example 7 An attempt was made to fabricate an LED substrate in the same manner as in Example 2, except that the drilling process was performed using a mold press with a clearance of 80 μm between the male and female dies. However, the laminate could not be sufficiently adhered to the base material, and an LED substrate could not be fabricated.
[0090] [Table 1-1]
[0091] [Table 1-2]
[0092] [Table 2] [Industrial Applicability]
[0093] According to the present invention, it is possible to provide an LED substrate that can be suitably used in a mini LED type backlight. [Explanation of symbols]
[0094] 1 LED board 2 Base material 3 reflective layer 4 Adhesive layer 5 LED light source 6. Projection height (P) 7. Baseline 8 1.0mm area around through hole 9 Ridges 10 Maximum point of ridge 11 Height of the ridge (h) 12 Adhesive layer thickness (t) 13 Peeling layer 14 Through hole
Claims
1. An LED substrate having an LED light source and a reflective layer on at least one surface of a substrate, The reflective layer comprises a white pigment, the reflective layer is attached to the base material via an adhesive layer, and the height (P) of the protruding portion of the LED light source from the reflective layer is 20 μm or more and 200 μm or less; The reflective layer has one or more through holes and a protrusion protruding toward the adhesive layer within a 1.0 mm area around the through hole, and the ratio (t / h) of the height (h) of the protrusion to the thickness (t) of the adhesive layer is 0.20 or more and less than 2.
00. LED board.
2. The LED substrate according to claim 1 , wherein the reflective layer has a thickness of 20 μm or more.
3. 3. The LED substrate according to claim 1, wherein the reflective layer is a biaxially oriented film.
4. 3. The LED substrate according to claim 1, wherein the reflective layer is composed mainly of a polyester resin, and the average void content in a cross section perpendicular to a layer surface of the reflective layer is 10% or more and 70% or less.
5. 3. The LED substrate according to claim 1, wherein a ratio (H2 / H1) of a height (H1) of the LED light source to a height (H2) of the reflective layer is 0.1 or more and 0.8 or less.
6. 3. The LED substrate according to claim 1, wherein the LED light source is disposed through the through hole in the reflective layer, and a ratio (Sl / Sh) of an area of the LED light source (Sl) to an area of the through hole (Sh) when observed from directly above a surface of the base material is 0.25 or more and less than 1.
00.
7. The LED substrate according to claim 1 , wherein a three-dimensional surface roughness SRa of the surface of the reflective layer opposite to the base material is 300 nm or more and less than 2000 nm.
8. The LED board according to claim 1 , wherein the LED light source is a blue LED light source.
Citation Information
Patent Citations
Metal substrate and light-emitting diode encapsulation method of metal substrate
CN101820044A
Active type silencer
JP1996016175A
Light reflecting film
JP2003160682A
Light-emitting module
JP2012069749A
Polyester film for light reflector
JP2013136232A
Cited By
LED Lighting Apparatus Including a Reflective Layer Having Perforation Structures for Mixed-Type SMD and CSP Chips
KR102854588B1